PEMBERDAYAAN MASYARAKAT MELALUI KELOMPOK WANITA TANI (KWT SAFAMARWA) DALAM PEMANFAATAN PEKARANGAN UNTUK MENINGKATKAN EKONOMI KELUARGA DI KELURAHAN CIGUGUR TENGAH KOTA CIMAHI - Rizki Arya Nugraha; Nandang Rukanda; Dewi Safitri Elshap (IKIP Siliwangi, 2026)
This study aims to describe the role of the Safamarwa Women's Farmers Group (KWT) in improving family economics, women's skills and participation, the use of local resources in empowerment activities, and supporting and inhibiting factors in home garden utilization. The method used was descriptive. Data collection techniques were conducted through observation, interviews, and documentation. The results indicate that the Safamarwa Women's Farmers Group positions women as key actors in household and community agricultural activities. Women act not only as implementers but also as managers, innovators, and decision-makers. Activities such as planting, managing seed gardens, and processing harvests into processed products demonstrate increased skills and participation of women. The use of local resources such as limited land, household wastewater, and organic materials supports the sustainability of agricultural activities. Factors supporting the KWT's success include institutional support, social capital, and active member participation. Meanwhile, inhibiting factors identified include limited time for female members and obstacles in product marketing. These findings demonstrate that the Safamarwa Women's Farmers Group plays a significant role in community-based women's empowerment and local resource-based empowerment.